Making Christian history : Eusebius of Caesarea and his readers - Hollerich, Michael J. (Christianity in late antiquity (North American Patristics Society), 2021)
"Known as the "Father of Church History," Eusebius was bishop of Caesarea in Palestine and the leading Christian scholar of his day. His Ecclesiastical History is an irreplaceable chronicle of Christianity's early development, from its origin in Judaism, through two and a half centuries of illegality and occasional persecution, into a new era of tolerance and favor under the Emperor Constantine. In this book, Michael J. Hollerich recovers the reception of this text across time. As he shows, Eusebius adapted classical historical writing for a new "nation," the Christians, with a distinctive theo-political vision. Eusebius's book left its mark on Christian historical writing from late antiquity to the early modern period, across linguistic, cultural, political, and religious boundaries, until its encounter with modern historicism and postmodernism. Making Christian History demonstrates Eusebius's vast influence throughout history, not simply in shaping Christian culture but also as his work itself has become contested territory as that culture has been constantly reevaluated, reformed, and resisted over the past 1,700 years"--